2022
DOI: 10.1371/journal.pone.0264766
|View full text |Cite
|
Sign up to set email alerts
|

Survival of immature pre-adult Gnathostoma spinigerum in humans after treatment with albendazole

Abstract: Human gnathostomiasis is a food-borne zoonotic helminthic infection widely reported in Latin America, Asia and Southeast Asia, particularly in Thailand. There are increasing reports of the parasite in countries where it is not endemic. A study of the survival drug-treated immature stage (STIM) of Gnathostoma spinigerum recovered from infected patients focused on their integument surface using scanning electron microscopy (SEM). STIM displayed a specific, characteristic head bulb, with a pair of large thick equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides, a recent study on Gnathostoma spinigerum reported the survival of immature preadult worm in human following albendazole treatment [64]. In that study, alteration on integument surfaces was noticed from surviving albendazole-treated larvae, postulated structural adaptation induced by the worm to protect against effect of albendazole.…”
Section: Plos Onementioning
confidence: 92%
“…Besides, a recent study on Gnathostoma spinigerum reported the survival of immature preadult worm in human following albendazole treatment [64]. In that study, alteration on integument surfaces was noticed from surviving albendazole-treated larvae, postulated structural adaptation induced by the worm to protect against effect of albendazole.…”
Section: Plos Onementioning
confidence: 92%
“…Some cases may respond well to corticosteroids alone, without anthelminthic treatment ( Smith et al, 2021 ). For our patient, ivermectin (0.2 μg/kg) was administered as an alternative medication instead of albendazole for two consecutive days, following recommendations for treating gnathostomiasis ( Nontasut et al, 2005 ; Kanjanapruthipong et al, 2022 ). Albendazole and ivermectin monotherapy or in combination have been effective with initial experienced treatment failure ( Chappuis et al, 2001 ; Parola et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…New migratory lesions refer to the persistence of living parasites which would require the initiation of a new course of treatment. Challenges also involve cerebral edema; hence oral steroids are advisable [172] .…”
Section: Gnathostomiasismentioning
confidence: 99%